Low temperature synthesis of ternary metal phosphides using plasma for asymmetric supercapacitors. (May 2017) - Liang, Hanfeng; Xia, Chuan; Jiang, Qiu; Gandi, Appala N.; Schwingenschlögl, Udo; Alshareef, Husam N.
Abstract: We report a versatile route for the preparation of metal phosphides using PH3 plasma for supercapacitor applications. The high reactivity of plasma allows rapid and low temperature conversion of hydroxides into monometallic, bimetallic, or even more complex nanostructured phosphides. These same phosphides are much more difficult to synthesize by conventional methods. Further, we present a general strategy for significantly enhancing the electrochemical performance of monometallic phosphides by substituting extrinsic metal atoms. Using NiCoP as a demonstration, we show that the Co substitution into Ni2 P not only effectively alters the electronic structure and improves the intrinsic reactivity and electrical conductivity, but also stabilizes Ni species when used as supercapacitor electrode materials. As a result, the NiCoP nanosheet electrodes achieve high electrochemical activity and good stability in 1 M KOH electrolyte. More importantly, our assembled NiCoP nanoplates//graphene films asymmetric supercapacitor devices can deliver a high energy density of 32.9 Wh kg −1 at a power density of 1301 W kg −1, along with outstanding cycling performance (83% capacity retention after 5000 cycles at 20 A g −1 ). This activity outperforms most of the NiCo-based materials and renders the NiCoP nanoplates a promising candidate for capacitive storage devices. Graphical abstract: Highlights: NiCoP nanoplates on carbon paper were synthesized using plasma at low temperature. Co substitution significantly enhanced the reactivity and electrical conductivity of Ni2 P. High performance asymmetric supercapacitors based on NiCoP and graphene sheets were assembled.